The socio-economical impact of work related deaths: the problem of work precarization. (30th September 2020) - Komoda, D; Martins, A C A; Cordeiro, R C; Gerônimo, C; Fernández, M R B; Smania, T G; Ruiz, A M P
Abstract: According to ILO, 6000 people die of work-related conditions. In Brazil, 4th in the rank of deaths related to work, 1 person day each 4 hours due to fatal accidents related to work (FARW). This study is an attempt to provide an overview on the impact of FARW in the family of the deceased workers. This is an epidemiological study, part of a research, conducted by epiGeo, in the city of Campinas, Brazil, 2015 and 2020, when the families of 73 workers (out of 82) that died of FARW were interviewed. The aim of the interviews was to evaluate the social impacts of FARW in the families, considering pre-determined parameters as follows. Out of 73 families interviewed, 15 (20.83%) of them didn't have access to the national social compensations, due to informality. Although 58 of the workers contributed to the national social security system, only 38 (65.55%) of them had access to social security pensions due to the death of their relatives. Regarding income, 47 families (64.38%) reported impacting decrease in income, and 5 of them (6, 8%) reported extreme economical hardship. In the last two years Brazilian national policy regarding work-related rights has been changing greatly. According to the Brazilian Geography and Statistics Institute (IBGE), the number of informal jobs had achieved an astonishing record number of 11.7mi workers in 2019, which can have impacts not only on the informalization and precarization of work which will also increase the difficulties to the access to the social security system rights. Further research should be conducted to understand why people are not having access to their social security rights. Health policy makers and health personnel must be aware of the impact on workers health and working conditions, caused by work precarization legislations. The socio-economic impact of work related deaths: the problem of work precarization. Key messages: The precarization of work caused by work-related legislative reforms can cause severe impacts on social security access. Families of workers that died of work-related fatal accidents have an important negative impact on income.